Zmiany sytuacji finansowej po fuzji na przykładzie spółki akcyjnej z branży owocowo-warzywnej - Żak, Agata (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The mergers become more frequently alternative of development for the companies from fruit and vegetable industry. The paper aims to analyze the changes in the structure of balance sheet as well as profit and loss accounts after the company’s merger. The influence of the merger on effectiveness and financial ratios of company were examined. The analysis results don’t show financial diffi culties typical for the described in the literature situation after merger of two companies. The results show the financial position of the examined company from fruit and vegetable industry improved in the year after the merger